(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
In spite of the scarce behavior-analytic literature regarding the creativity, B. F. Skinner’s considerations along his work about creative behavior allow approaching relevant aspects of the phenomenon. The aim of the present study consists of systematizing Skinner’s approach, taking three themes as reference: the creative behavior in problem solving, the creative behavior in the verbal behavior, and the learning of creative behavior in teaching institutions. Starting from the presentation of Skinner’s approach, the creative response is pointed as the product of the same determination processes that explain other classes of operant responses, and contingencies that promote the variability of behavior play a fundamental role for the occurrence of creative behavior.